Effects of time‐based administration of abstinence reinforcement targeting opiate and cocaine use. Issue 3 (6th April 2020) - Toegel, Forrest; Holtyn, August F.; Subramaniam, Shrinidhi; Silverman, Kenneth
Abstract : Polydrug use is a common problem among patients in opioid‐substitution treatment. Polydrug use has been reduced by administering abstinence‐reinforcement contingencies in a sequence, such that a single drug is targeted until abstinence is achieved, and then an additional drug is targeted. The present study examined effects of administering abstinence‐reinforcement contingencies sequentially based on time rather than on achieved abstinence. Participants accessed paid work (about $10/hr maximum) in the Therapeutic Workplace by providing urine samples 3 times per week. The urine samples were tested for opiates and cocaine. During an induction period, participants earned maximum pay independent of drug abstinence. Then, maximum pay depended upon urine samples that were negative for opiates. Two weeks later, maximum pay depended upon urine samples that were negative for both opiates and cocaine. Opiate and cocaine abstinence increased following administration of the respective contingencies. The time‐based administration of abstinence reinforcement increased opiate and cocaine abstinence.